The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1507/endocrj.k07-101
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen Suppresses Retinaldehyde Dehydrogenase 1 Expression in the Anterior Pituitary Glands of Female Rats

Abstract: Abstract. Retinoic acid (RA) plays a critical role in cell growth and tissue development. RA is also a regulating factor of pituitary function. RA is synthesized from retinoids through oxidation processes. The oxidation of retinal to RA is catalyzed by the retinaldehyde dehydrogenases (RALDHs), including RALDH1, RALDH2 and RALDH3. Recently, we demonstrated that RALDH1 is expressed in the anterior pituitary glands of adult male rats. However, the expression of RALDH1 in the female pituitary gland and the regula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 17 publications
2
5
0
Order By: Relevance
“…In previous studies, we reported that RA-synthesizing enzyme, retinaldehyde dehydrogenase 1, was expressed in folliculostellate cells and lactotrophs but not in somatotrophs [22,23]. In the present study, we found that RA increased Ghrh-r and Ghs-r gene expression and promoted GHRH-and ghrelin-induced GH release from isolated rat anterior pituitary cells.…”
Section: Discussionsupporting
confidence: 58%
“…In previous studies, we reported that RA-synthesizing enzyme, retinaldehyde dehydrogenase 1, was expressed in folliculostellate cells and lactotrophs but not in somatotrophs [22,23]. In the present study, we found that RA increased Ghrh-r and Ghs-r gene expression and promoted GHRH-and ghrelin-induced GH release from isolated rat anterior pituitary cells.…”
Section: Discussionsupporting
confidence: 58%
“…For normalization, we also quantified β-actin using forward (5'-tGG CAC CAC ACt ttC tAC AAt GAG C-3') and reverse (5'-GGG tCA tCt ttt CAC GGt tGG-3') primers. gland of female rats [19]. our in vivo study indicated that estrogen is a candidate for regulator of RALdh1 expression in the pituitary, but the mechanisms that may be responsible for this effect are not understood.…”
Section: Quantification Of Raldh1 Mrna Levels By Real-time Reverse Trmentioning
confidence: 78%
“…this decrease in RALdh1 expression was observed in cells incubated with a 17β-estradiol concentration as low as 1 x 10 -14 M. Lieberman et al [29] reported a dose-dependent increase in prolactin synthesis at physiological concentrations of estradiol (1 x 10 -11 -1 x 10 -6 M) in a rat pituitary cell culture. We previously reported that RALdh1 mRnA expression in the pituitary gland of ovariectomized rats was suppressed after a single subcutaneous injection of 17β-estradiol: mRnA expression in response to 0.01, 0.1, 1, 10, and 100 μg of 17β-estradiol decreased by 13%, our recent work has shown that RALdh1 mRnA expression level in the pituitary gland is lower in female than in male rats [19]. Moreover, we observed that RALdh1 mRnA expression was lower in female rats treated with 17β-estradiol [19].…”
Section: Treatment With Er Antagonist and Agonistsmentioning
confidence: 88%
See 1 more Smart Citation
“…In situ hybridization was performed with digoxigenin (DIG)-labeled cRNA probes, as described in our previous report [9]. Antisense and sense cRNA probes of rat MK were synthesized by in vitro transcription with DIG RNA Labeling Mix (Roche Diagnostics, Penzberg, Germany) [10].…”
Section: In Situ Hybridization and Immunohistochemistrymentioning
confidence: 99%